TENSES USAGE IN PRE- AND POST-TEST COMPOSITIONS OF INTENSIVE COURSE PROGRAM - DIPTA, DINAR (RETAIN : Journal of Research in English Language Teaching, 2013)
Tense adalah bagian dari tata bahasa yang harus dikuasai oleh siswa untuk mendukung kemampuan berbahasa Inggris. Dengan menggunakan tense, siswa dapat memahami hubungan antara bentuk kata kerja dengan konsep waktu ketika suatu tindakan terjadi. Kesalahan penggunaan tenses sebagian besar muncul dalam bahasa tulis karena menulis dianggap sebagai keterampilan yang paling sulit dalam bahasa Inggris. Penelitian ini bertujuan untuk menganalisis penggunaan tenses dalam karangan siswa IC. Selanjutnya, penelitian ini menyelidiki apakah siswa menggunakan tenses yang lebih akurat dalam pos-tes dibandingkan pre-tes dan tenses apa yang paling sulit dikuasai. Penelitian ini adalah penelitian deskriptif kuantitatif. Subyek penelitian ini adalah mahasiswa tahun pertama Jurusan Bahasa Inggris di Unesa. Data penelitian adalah dokumen karangan siswa IC. Teknik analisis yang digunakan adalah analisis deskriptif yaitu mengidentifikasi tenses, mengevaluasi kesalahan, dan menarik kesimpulan yang disajikan dalam bentuk tabel dan kalimat. Hasil penelitian menunjukkan bahwa siswa menemui kesulitan dalam menyusun pola tense tertentu. Kata Kunci: tense, tense akurat, intensive course, karangan. Abstract Tense as a part of grammar should be mastered by the students to support the English skills ability. Tenses make learners understand the relationship between the form of the verb and the concept of time which an action happened. Error in the use of tenses mostly appears in written language since writing is considered as the most difficult skill in English. The study aims to analyze the use of tenses in IC students’ composition. Furthermore, the study investigated whether or not the students use more correct tenses in the post-test than in pre-test and what tenses are difficult to master by the IC students. The study was a descriptive quantitative research. The subject of the study was the first year students of English Department in State University of Surabaya. The data of the study were the document of IC students’ compositions. The analysis technique used descriptive analysis, identifying the tenses, evaluating the error, and drawing the conclusion in form of tables and sentences. The result of the study showed that the students were found difficulties in using certain tense form. Keywords: tense, accurate use of tense, intensive course, composition.